PERTUMBUHAN BENIHIKAN BAUNG (Hemibagrus nemurus) DALAM KERAMBA JARING APUNG YANG DIBERI PAKAN BUATAN DENGAN KADAR PROTEIN BERBEDA [Growth of green catfish (Hemibagrus nemurus) fry in floating net cage feed by artificial food with different protein content] - Ningrum Suhenda; Reza Samsudin; Estu Nugroho (Jurnal Iktiologi Indonesia, 2010)
The study was conducted to evaluate different protein content of feed on the growth performances of green catfish (Hemibagrus nemurus). Two thousands fingerlings (3.92 ± 0.32 g in averaging of individual body weights) were stocked in each of floating net cage (3x3x3) m3. They were fed daily for four months with diets containing protein content of 27% and 31%. The feed was given in pellet form at 4-8 % of total body weight. Result of this study showed that the fish feed with 31 % protein content gave better growth performances than it with 27 % protein feed. The feed contain of 31% protein was optimum for green catfish fingerlings and gave a higher average individual weight gain (80.48 g), specific growth rate (2.67%), fat retention (29.48%), and better feed conversion ratio (2.28). Survival rates were si-milar for two treatments and ranged between 94.17 to 95.18%.